2015
DOI: 10.5897/jpp2014.0338
|View full text |Cite
|
Sign up to set email alerts
|

Herbal medicines use among diabetic patients in Oriental Morocco

Abstract: The aim of this study was to determine the prevalence of herbal medicines (HM) use among diabetic patients in Oriental Morocco, in order to establish an updated inventory of HM consumption and determine the predictive factors of their use in our patients. We conducted a cross-sectional study during three months from March, 2013 to May, 2013 including all diabetic patients consulting at the Department of Endocrinology and Metabolism of Mohammed VI University Hospital in Oujda. The study included 279 diabetics (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 28 publications
0
11
1
Order By: Relevance
“…The multivariate analysis in our study showed that secondary/tertiary education was an independent predictor of herbal medicine use. This finding is in contrast to findings in Morrocco [49].…”
contrasting
confidence: 99%
“…The multivariate analysis in our study showed that secondary/tertiary education was an independent predictor of herbal medicine use. This finding is in contrast to findings in Morrocco [49].…”
contrasting
confidence: 99%
“…Myrtus communis L. BPRN60 Rihane 3 0.70 1.00 100.00 (Eddouks et al, 2002;Jouad et al, 2001b;Tahraoui et al, 2007;Ziyyat et al, 1997) ( Elfellah et al, 1984;Sepici et al, 2004) Eucalyptus globulus Labill. BPRN23 Kaliptus 6 1.40 2.00 50.0 (Eddouks et al, 2002;Jouad et al, 2004Jouad et al, , 2001bZiyyat et al, 1997) ( Mahmoudzadeh-Sagheb et al, 2010;Rachid et al, 2012;Telli et al, 2016) Oleaceae Olea europaea L. BPRN12 Zitoune 33 7.71 1.36 73.33 (Benkhnigue et al, 2014;Bousta et al, 2014;Eddouks et al, 2002;El Amrani et al, 2010;Jouad et al, 2001b;Orch et al, 2015;Tahraoui et al, 2007;Zayneb et al, 2015;Ziyyat et al, 1997) ( Amin et al, 2013;Eidi et al, 2004;Sato et al, 2007) Papaveraceae Papaver rhoeas L. BPRN54 Belaaman 1 0.23 1.00 100.00 (Eddouks et al, 2002;Katiri et al, 2017) (Allali et al, 2008 Pedaliaceae Sesamum indicum L. BPRN66 Zenjlane 3 0.70 2.00 50.00 (Eddouks, 2017;Eddouks et al, 2002;Jouad et al, 2001b;Tahraoui et al, 2007) ( (Eddouks et al, 2002;Jouad et al, 2001b;Tahraoui et al, 2007;Ziyyat et al, 1997) ( Bamosa et al, n.d.;...…”
Section: Myrtaceaementioning
confidence: 99%
“… Nafea Se Dec Oral 6.1 [ 18 , 22 – 24 , 39 , 44 , 48 , 49 , 60 ] [ 54 ] Pastinaca sativa L. Laft-mahfor R Raw Oral 3.7 [ 39 , 44 ] No Data Ammi visnaga (L.) Lam Bouchnikha Fr Dec Oral 0.8 [ 22 – 24 , 46 , 47 , 49 – 53 ] No Data Apocynaceae Nerium oleander L. Deflla L Fum Inhalation 04 [ 22 – 24 , 39 , 44 , 46 49 , 51 – 53 , 59 , 62 ] No Data Asteraceae Artemisia herba-alba Asso. ...…”
Section: Resultsmentioning
confidence: 99%